Over 6% Certified Sb2(S, Se)3 Solar Cells Fabricated via In Situ Hydrothermal Growth and Postselenization. (27th December 2018) - Wang, Weihuang; Wang, Xiaomin; Chen, Guilin; Yao, Liquan; Huang, Xiaojuan; Chen, Tao; Zhu, Changfei; Chen, Shuiyuan; Huang, Zhigao; Zhang, Yi
Abstract: Antimony sulfide‐selenide Sb2 (S, Se)3 as a promising absorber material has drawn extensive attention owing to its rewarding photoelectric properties, low toxicity, and earth abundant components. Here, an available and highly effective method, in situ hydrothermal growth accompanied with postselenization, is successfully applied to fabricate Sb2 (S, Se)3 solar cells. The rationale for the preparation of Sb2 S3 precursors by the hydrothermal method is discussed, and detailed characterization of Sb2 (S, Se)3 films selenized with different temperatures is also carried out. Finally, a solar cell with structure of FTO/CdS/Sb2 (S, Se)3 /Spiro‐OMeTAD/Au is fabricated, which delivers an encouraging 6.14% efficiency with V oc of 732 mV, J sc of 14.6 mA cm −2, and fill factor of 60.8%. This work provides valuable references for further development and improvement of Sb2 (S, Se)3 solar cells. Abstract : A hydrothermal method is successfully applied to fabricate high performance Sb2 (S, Se)3 solar cells . Meanwhile, Sb2 (S, Se)3 thin films with controllable bandgap gradient and relevant devices are successfully prepared and investigated. Finally, a device with the structure FTO/CdS/Sb2 (S, Se)3 /Spiro‐OMeTAD/Au achieves a power conversion efficiency of 6.14% with V oc of 732 mV, J sc of 14.6 mA cm −2, and a fill factor of 60.8%.